SIMULASI GERAK ULAR MENGGUNAKAN METODE INVERSE KINEMATICS - Agung Dwi Saputro; Mohammad Suyanto; Sukoco Sukoco (Universitas Janabadra, 2018)
Simulation of snake motion using inverse kinematics method is a research that aims to know how the motion of snake animal that will be applied in 3D animation. To know how snake animal motion data needed is angle of bone animal freedom degree and also motion pattern of snake animal by using inverse kinematics method. Limitation of variables in this study is the object of research using snake king snake type, the method used using inverse kinematics and simulation methods created using Maya software. The method of analysis used in this method is the method of research and development.This research produces data on snake animal walks and border degrees of freedom data to be applied in 3D animation. The end result of this research is the path pattern of the snake animal, the 3D simulation produced in the form of walking movement.The conclusion of this research is the application of inverse kinematics method can be applied in simulation of 3D motion of snake animal. This study yields data in the form of angle of bone freedom. Produce snake animal pattern shaped like a curve or the letter S. Keyword: Inverse Kinematics, Snake, Degrees of Freedom